Association of OXTR rs53576 with the Developmental Trajectories of Callous-Unemotional Traits and Stressful Life Events in 3- to 9-Year-Old Community Children. - Ezpeleta, Lourdes; Penelo, Eva; de la Osa, Núria; Navarro, J. Blas; Fañanás, Lourdes; Fatjó-Vilas, Mar (Journal of Abnormal Child Psychology, 2019)
The objective was to obtain developmental trajectories combining callous-unemotional traits and the number of stressful life-events between ages 3 and 9 years and to ascertain their association with the polymorphism rs53576 at the Oxytocin Receptor gene (OXTR). A total of 377 children were assessed yearly from ages 3 to 9 years. Latent class growth analysis for parallel processes was used to identify distinct trajectories for callous-unemotional traits (assessed using the Inventory of Callous-Unemotional Traits, ICU) and number of stressful life-events, and then the influence of being an A allele carrier on class membership was included with OXTR genotypes as a binary time-invariant predictor, following a 3-step approach. A 3-class model showed the highest entropy (.859) and adequate posterior probabilities of class membership (≥.884). Class 1 (n = 226, 59.9%) included children with low and stable ICU scores and low and descending stressful life-events; class 2 (n = 127, 33.7%) included children with high and ascending ICU scores and low and slightly descending stressful life-events; and class 3 (n = 24, 6.4%) included children with persistently high profiles both for ICU scores and stressful life-events. Carrying an A allele (genotypes GA/AA) increased the odds of pertaining to class 3 (high and persistent ICU scores and stressful life-events) as opposed to class 2 (OR = 4.27, p = 0.034) or class 1 (OR = 3.81, p = 0.042). The results suggest the importance of considering callous-unemotional traits and stressful life-events in conjunction. In addition, the genetic variability of OXTR (rs53576) may help to understand individual differences in early development.